I will go with you (con te partiro) - Summer, Donna; Hector, Hex; Sony Music Entertainment (New York : Sony Music Entertainment, 1999)
Contains two versions of the single taken from the album VHI Presents, Live & More Encore!.
CD 1 : Radio edit (3:58) -- Album version (4:10).
Koleksi Khas Wiramanja.
Title from disc label.
Keywords: Songs, English